Rewriting Torture: Manufacturing a Primer of Abuse in US Domestic Prisons - Phillips, Susan A. (Social justice, 2016)
A college-level critical pedagogy project confirms that human rights reporting can play a role in prison abolition as opposed to reform. By writing an altered version of the ICRC torture papers, students compared US prison torture in domestic and military sites, confirmed the application of a torture label to US prisons, decentered the classroom, and shifted foundational categories, including those around a capital crime. Creating counter-narratives partly based on the perspectives of the prisoners themselves extends the radical potential of human rights work. When combined with critical pedagogy, human rights writing can help create anti-carceral praxis.